2000
DOI: 10.1046/j.1365-2125.2000.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

The rates of common adverse events reported during treatment with proton pump inhibitors used in general practice in England: cohort studies

Abstract: Aims To estimate the rates of common adverse events in patients treated with the proton pump inhibitors omeprazole, lansoprazole and pantoprazole in general practice in England. Methods In prescription‐event monitoring cohort studies, data on dispensed prescriptions prescribed by general practitioners in England soon after each drug was launched were linked to subsequent clinical events recorded by the prescriber. 16 205 patients prescribed omeprazole between June 1989 and June 1990, 17 329 patients prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 27 publications
1
42
0
3
Order By: Relevance
“…This confirms the experience of controlled clinical trials and previous adverse event studies which shows that proton pump inhibitors are safe and can be used without safety concerns regarding their potential for interaction. 7,13 We concentrated in particular on vitamin K antagonist interactions, as these are reported more frequently than all other interactions combined and are also important from a theoretical perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms the experience of controlled clinical trials and previous adverse event studies which shows that proton pump inhibitors are safe and can be used without safety concerns regarding their potential for interaction. 7,13 We concentrated in particular on vitamin K antagonist interactions, as these are reported more frequently than all other interactions combined and are also important from a theoretical perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of their excellent safety record, the relative safety of different proton pump inhibitors has been widely publicized over the last few years, with particular emphasis on drug-drug interactions. [1][2][3][4][5][6][7][8][9] It has been suggested that pantoprazole is less likely than omeprazole or lansoprazole to interact with other drugs as a result of minor differences in its metabolic profile. 10,11 In a recent retrospective survey of patient treatment records from US veterans, it was concluded that the co-prescription of omeprazole or lansoprazole with warfarin, clarithromycin or diclofenac led to an increase in adverse events, requirements for care and total costs of care.…”
Section: Introductionmentioning
confidence: 99%
“…However, overall incidence of adverse effects mentioned above remains very low. In general PPIs as well as H 2 -antagonists represent drug classes with favorable safety profi le (36).…”
Section: Discussionmentioning
confidence: 99%
“…Ils touchent moins de 5 % des patients traités par IPP et disparaissent rapidement à l'arrêt du traitement [3].…”
Section: Introductionunclassified